Effect of Local Steroid Injection on Prevertebral Soft Tissue Swelling Following Anterior Cervical Discectomy and Fusion - Seddighi, Afsoun; Nikouei, Amir; Seddighi, Amir Saied; Arjmand, Yasaman (International Clinical Neuroscience Journal, 2017)
Background: Prevertebral soft tissue swelling (PSTS) following anterior cervical surgery, may proceed to airway compromise which is potentially lethal. We plan to evaluate the effect of local steroid injection to reduce PSTS after anterior cervical discectomy and fusion (ACDF). Methods: In a randomized clinical trial 66 patients who underwent ACDF involving one to three segments due to radiculopathy or myelopathy were enrolled and randomly divided to two groups of 38 with local injection of 80 mg methylprednisolone in operation site, and control. Prevertebral soft tissue thickness to mid anteroposterior vertebral body diameter (S/V) ratio was defined to assess PSTS. In addition, dysphagia and pain at surgery site was evaluated using Bazaz dysphagia scale and Visual Analogue Scale (VAS) respectively, at 1st, 5th and 10th post-operative days. Results: We have observed significantly lower S/V ratio in all studied vertebrae, except C6 on second postoperative day in case group. At the end of the 6th month, there was no significant difference for S/V ratio in any level in two groups. Severity of dysphagia was significantly lower in 1st, 5th and 10th post-operative day in patients in case group. (P value<0.05) Also, patients in case group experienced significantly less severe odynophagia at 1st, 5th and 10th post-operative day, which was assessed by VAS. (P value<0.05) Conclusions: The use of local methyl prednisolone in prevertebral space is a simple and effective method to reduce PSTS and severity of dysphagia and odynophagia. Furthermore, this method was not associated with any adverse effects.